We, ourselves and us: Tensions of identity, intersubjectivity and positionality stemming from the people and dancefloors project - Zampini, Giulia Federica; Buck-Matthews, Eveleigh; Killick, Anthony; Salter, Lee (The International journal of drug policy, 2021)
Grounded in intersubjective participatory action research, the people and dancefloors project has sought to produce a space for the co-creation of knowledge about dancefloors and drug taking, building a platform for developing insights from the positionality of current drug users. Through film, it provides hermeneutic insight while legitimising their voices. In this paper, we share some reflections as researchers/users/activists arising from our involvement in the project. To begin with, we reflect on the motivations for the project, and the epistemic suppositions that animated it. This is followed by conversational style interviews where we re-evaluate our position in light of the project, with a particular focus on the tensions that drug use introduces between professional, personal and political domains in our lives. These reflections are useful to people who use drugs and hold privilege by nature of their social and cultural position. While questioning the silencing of personal experiences in relation to drug use, we also react to some of the traditional tendencies of academia, including institutionalised individualism, which isolates researchers and discourages them from finding political collectivity, and the subjectivist/objectivist dichotomy, which supports a tendency to objectify research participants while removing the self from the equation. Despite the challenges that arise from disentangling our multiple experiences and identities, our intersubjective dialogue inspires deeper learning about ourselves and each other, encouraging us towards a more openly political stance.